pen repeat sequences are GGN clusters and encode a glycine-rich domain in a Drosophila cDNA homologous to the rat helix destabilizing protein. - Haynes, S.R.; Rebbert, M.L.; Mozer, B.A.; Forquignon, F.; Dawid, I.B. (Proceedings of the National Academy of Sciences of the United States of America, 1987)
Several cDNA clones that contain the pen repeat have been isolated and sequenced; pen consists of clusters of GGN triplets, where N can be any nucleotide. Some of the pen repeat sequences are found within long open reading frames in which they encode oligoglycine stretches. For one of the clones, the deduced amino acid sequence of the entire open reading frame, especially in the region preceding the glycine-rich domain, shows strong homology to the rat helix destabilizing protein [Cobianchi, F., SenGupta, D. N., Zmudzka, B. Z. & Wilson, S. H. (1986) J. Biol. Chem. 261, 3536-3543]. The rat protein and homologs in other organisms are single-stranded nucleic acid binding proteins, some of which are major components of heterogeneous nuclear ribonucleoprotein particles. We suggest that we have cloned a cDNA encoding a Drosophila single-stranded nucleic acid binding protein.